A fusion protein composed of the DSL domain of Dll1 and RGD motif protects cryptic stem cells in irradiation injury. Issue 2 (9th March 2018) - Sun, Zhi-Jian; Zhang, Yi-Zhe; Liu, Fan; Chen, Juan-Juan; Chen, Dong-Xue; Liu, Hong-Bao; Liang, Liang; Han, Hua
Abstract : Intestine is vulnerable to irradiation injury, which induces cell death and compromises regeneration of intestinal crypts. It is well accepted that cryptic stem cells, which are responsible for cryptic regeneration under physiological and pathological conditions, are controlled by multiple cell-intrinsic and environmental signals such as Notch signaling. Therefore, in the present study, we tested whether a soluble Notch ligand tethered to endothelial cells—mD1R—the Delta–Serrate–Lag2 (DSL) domain of mouse Notch ligand Delta-like1 fused with a RGD motif could protect cryptic cells from irradiation-induced intestinal injury. The result showed that administration of mD1R, which activated Notch signaling in intestinal cells, ameliorated loss of body weight and reduction of cryptic structures in intestine after total body irradiation (TBI) in mice. Histological staining showed that injection of mD1R after TBI promoted cryptic cell proliferation and reduced cell apoptosis in crypts. Immunofluorescence staining and reverse transcription (RT)-PCR showed that mD1R increased the level of Lgr5, Bmi1, Olfactomedin-4 (OLFM4), and IRIG1 in crypts, suggesting a protective effect on cryptic stem and progenitor cells after irradiation. Moreover, we found that administration of mD1R increased the number of Paneth cells and the mRNA level of Defa1, and the number Alcian Blue+ Goblet cells decreased first and then increased after irradiation, suggesting that mD1R promoted the maturation of the intestinal crypt after irradiation injury. Our data suggested that mD1R could serve as a therapeutic agent for the treatment of irradiation-induced intestinal injury.